The effect of exercise on cardiovascular disease risk factors in sedentary population: a systematic review and meta-analysis - Guo, Liangru; Wang, Chaochao (Frontiers in Public Health, 2025)
ObjectiveThe aim of this study (PROSPERO CRD42023443860) was to determine the dose–response associations of exercise on cardiovascular disease risk factors in sedentary populations using systematic evaluation and meta-analysis.MethodsWe conducted a systematic search of the literature up to July 2024 using PubMed, Web of Science, and SCOPUS. Of the 72,704 search records initially identified, 15 studies were considered eligible for systematic evaluation and meta-analysis. The methodological quality of the included literature was assessed using the Cochrane Risk Assessment Tool. Using a random-effects model, we pooled standardized mean differences (SMDs) with 95% confidence intervals (CIs) for key cardiovascular risk factors.ResultsExercise improved systolic blood pressure [SMD = −0.33 (95% CI, −0.62 to −0.05), p = 0.02], diastolic blood pressure [SMD = −0.52 (95% CI, −0.92 to −0.12), p = 0.01], and resting heart rate [SMD = −0.30 (95% CI, −0.50 to −0.10), p = 0.004]. However, no significant effects were observed for total cholesterol [SMD = −0.03 (95% CI: −0.24 to 0.18), p = 0.78], HDL cholesterol [SMD = 0.06 (95% CI: −0.16 to 0.27), p = 0.6], LDL cholesterol [SMD = −0.21 (95% CI: −0.59 to 0.18), p = 0.29], triglycerides [SMD = −0.11 (95% CI: −0.42 to 0.21), p = 0.51], or body mass index [SMD = 0.01 (95% CI: −0.16 to 0.17), p = 0.94].ConclusionRegular exercise with a duration of 30–40 min per session and a frequency of 3–5 sessions per week significantly improves blood pressure and resting heart rate in sedentary populations, but does not appear to affect lipid profiles or body mass index.